Pengaruh Perilaku boikot terhadap minat pembelian konsumen (studi kasus PT. Unilever Tbk) - Saputri, Nurliana Nanda; Agung Rizki Putra, Rafita Rafita, Anggreni Anggreni, Bintang Ramadhan, (Jurnal Mirai Management, 2025)
This study aims to analyze the effect of boycott behavior on consumer purchasing interest in PT Unilever Tbk products. This research uses a quantitative approach by distributing questionnaires to 71 respondents of Economics Study Program students, Bangka Belitung University. The research tools used are descriptive tabulation analysis and simple linear regression analysis using the data processing application, Stata 17. The results of the two analyses used show that boycott behavior affects consumer purchasing interest. The majority of respondents stated that social and ethical issues were the main reasons they boycotted, although product quality and reputation were still important considerations in purchasing decisions. These results suggest that consumers are increasingly considering moral values in their consumption activities.